Mecanismos de asignación de permisos para el uso del espectro radioeléctrico y su efecto en la brecha digital (2020)
The spectrum is a natural resource indispensable for the deployment of telecommunication’s infrastructure, managed and regulated by central governments. Given the importance of this resource, this study defines a dynamic model with an instrumental variable that explains the effect of efficient spectrum allocation on the mobile price basket, based on a panel for one hundred and seven countries between 2008 and 2018. The results of the model suggest that efficient spectrum allocation may decrease the value of the mobile basket by 4,91 dollars. In other words, an efficient spectrum allocation influences well-being, due to the fact that it makes mobile services more accessible to all citizens, and thus contributes to the closure of the digital divide.